Peran Etika Kerja Islami dan Locus Of Control Dalam Meningkatkan Kepuasan Kerja Pegawai (Studi Pada Satuan Kerja Perangkat Daerah (SKPD), Kab. Buton Utara) - Muhamad Ridhayantho; Noermijati Noermijati; Dodi W. Irawanto (Forum Manajemen Indonesia (FMI), 2015)
This study aims to identify and analyze the role of Islamic Work Ethic and locus of control in improving job satisfaction both directly and indirectly. The study population is 607 Muslim Civil Servants (PNS) and working in regional work units (SKPD) North Buton Regency. The sample that obtained for this study are 124 civil servants (PNS). Sampling was done by using a proportional (proportionate random sampling), in each instances, with 8% of precision rate. The data collection method was a customized questionnaire survey method based on Likert scale 1-5. The analysis tool used is Partial Least Square (PLS) with hypothesis testing process used software application program Smart PLS 3.0.The results showed that the Islamic Work Ethic and Locus Of Control has a positive and significant influence either directly or indirectly on Job Satisfaction, thus concluded that the Islamic work ethics and locus of control proved to increase employee satisfaction in work units (SKPD) , North Buton Regency. The practical contribution of this research is to provide information to the Civil Servants (PNS) and Local Government in order to always improve understanding and programs related to the increase in work attitudes Civil Servants (PNS), especially in the scope of work units (SKPD). While theoretically this study contribute to the development of different models of measurement variables from previous studies, in which the role of the Islamic Work Ethic variables and Locus of Control as exogenous variables are reflective, while job satisfaction variables as endogenous variables are formative. Further limitations and suggestions discussed in the research. Keywords: Islamic Work Ethic, Locus of Control, Job Satisfaction.